Geometric parameters of a bluff body affecting vortex distribution that produces flutter - Nurul Affira, binti Sazali (Universiti Malaysia Sarawak (UNIMAS), 2015)
As the population of the world and economy grows, the demand for energy supply is increasing. Studies have been developed to invent the energy harvester in order to replace the power generators and batteries. Flutter has been suggested as an input source for energy harvesters due to its potential capacity for harvesting electrical power. Generating electricity from wind creating aerodynamic flutter opens up a wide opportunity for generating and consuming energy locally. Many studies have been done in order to produce classical flutter which is an aeroelastic instability involving the deflection of the body. This study is speoifically to investigate the parameters that affect the vortex distribution that produces flutter. This approach is to study the vortex fonned and deflection of beam when flutter is produced. The study is done by doing simulation using ANSYS. It includes the exploration of the FLUENT setups to produce accurate and efficient results as well as to monitor the parameters needed to be taken into consideration. The addition of dimples on the cylinder has increase the vorticity of the system as well as the deflection when flutter is produced. By adding dimples, the value of deflection and vortex fonned will be different depending on the number of the dimples.